Cucurbitacin B, Purified and Characterized From the Rhizome of Corallocarpus epigaeus Exhibits Anti-Melanoma Potential - Aiswarya, Sreekumar Usha Devi; Vikas, Gowda; Haritha, Nair Hariprasad; Liju, Vijayasteltar Belsamma; Shabna, Anwar; Swetha, Mundanattu; Rayginia, Tennyson Prakash; Keerthana, Chenicheri Kizhakkeveettil; Nath, Lekshmi Raghu; Reshma, Mullan Vellandy; Sundaram, Sankar; Anto, Nikhil Ponnoor; et al. (Frontiers in Oncology, 2022)
The ethnomedicinal plant from the Cucurbitaceae family, Corallocarpus epigaeus, or its bioactive derivatives have been widely utilized in traditional medicine owing to their distinct applications against various human ailments and have lured the interest of ethnobotanists and biochemists. Here, we report for the first time, the anti-cancer potential of a bio-active fraction isolated from the dried rhizome of C. epigaeus, and the bioactive principle identified as cucurbitacin B (Cu-B). The purification processes involved utilization of multiple organic extracts of C. epigaeus rhizome powder, yielded Cu-B from the ECF bioactive fraction by the chromatographic separation of the ethyl acetate extract. Amongst the various cancer lines tested, melanoma cells exhibit maximal sensitivity towards the Cu-B-containing ECF fraction. Cu-B induces an apoptotic mode of cell death initiated intrinsically as well as extrinsically in A375 melanoma cells whilst remaining non-toxic to normal melanocytes. In vivo studies involving a NOD-SCID murine model of human melanoma demonstrate the ability of Cu-B to attenuate tumor growth whilst remaining pharmacologically safe in vivo, as assessed in Swiss albino mice. Furthermore, Cu-B inhibits MEK 1/2 as well as the constitutive and EGF-induced Erk 1/2 activation, indicating a definitive involvement of MAPK signal transducers in regulating Cu-B-mediated anti-melanoma activity. Together, our study demonstrates the anti-melanoma potential of C. epigaeus-derived Cu-B, which indicates the Cucurbitaceae succulent as a prospective source for deriving potent and pharmacologically safe anti-cancer compounds.